Theory And Practice Integration In The Implementation Of Innovative Technologies In Preschool Education And Quality Monitoring Mechanisms - Khasanova, Mohimbegim (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
The article highlights the importance of theory and practice integration and quality monitoring mechanisms in the process of introducing innovative technologies in the preschool education system of Uzbekistan. The study analyzed data from the State Statistics Committee, Ministry releases and international organizations (UNICEF, World Bank). The main attention was paid to coverage indicators in the field, the activities of digital platforms and the criteria used to assess quality. The results noted a significant increase in the coverage of preschool education during 2017–2024, the expansion of infrastructure and the acceleration of the use of digital resources. At the same time, it was found that the increase in coverage does not fully guarantee quality indicators, and the need for regular monitoring and teacher training was emphasized. At the end of the article, practical recommendations are given on the formation of a unified monitoring system, the widespread use of innovative methods, and the strengthening of parental cooperation for the sustainable improvement of the quality of education.